What is luxury hospitality? A need to move towards a scientific understanding - Andy Heyes (Research in Hospitality Management, 2021)
The world of luxury and that of luxury hospitality has been growing for numerous years. From hotels such as the Burj Al Arab in Dubai, The Torch in Doha and The Savoy in London, luxury hospitality and the variety which is now on offer are growing exponentially. Despite the growth of the industry, little research and literature is available to practitioners, scholars and researchers alike to help them better understand the current situation. While there is a little literature on offer, there is a need for more detailed research and analysis to be conducted. This article is a call for research which it is hoped will help to add to the current body of knowledge as well as help to attract future researchers to collaborate on developing new insights. A brief analysis of the current situation and literature is provided along with future tracks and themes which could potentially be a means for research development.